Qualitative Evaluation and Research methods. - "Patton, Michael Quinn." (New Delhi, 1990)
Once again setting the standard for the field, the Second Edition of Qualitative Evaluation Methods reflects the tremendous explosion of interest in qualitative methods over the past decade. Thoroughly revised and updated, this new edition includes three new chapters on Theoretic Foundations of Qualitative Inquiry, Particularly Appropriate Qualitative Applications and Quality and Credibility of Qualitative Analysis. Patton has also a completely updated literature review and citations section to reflect the mass of new research in qualitative methods in the last ten years. It will be of interest to anyone involved in evaluation of any kind.
Keywords: Social sciences Methodlogy